Knowledge of Information Security Awareness and Practices for Home Users: Case Study in Libya - Asker, Hamida; Tamtam, Abdalmonem (European Scientific Journal, ESJ, 2023)
The abundance of information available through the Internet, mobile applications, and cloud computing has made it convenient for users to access a wide range of information. However, this convenience comes with a cost as this information is constantly at risk of being compromised by cybercriminals and hackers. While the recognition of the potential dangers of information security is increasing in developed countries, in regions like Libya in North Africa, the level of protection for this information is insufficient. The purpose of this study is to examine the various factors that may influence or affect the users’ practice and awareness at home. The investigated factors are policy, behavior, training, knowledge of IT and education. In order to accomplish the goals of this study, a quantitative methodology was implemented. Specifically, a survey was created to assess the correlation between key factors and security awareness and practices in the home environment. The survey attracted 220 respondents and analyzed using Bivariate/Pearson Correlation to determine the relationship between the independent variable and the dependent variable. The result of the study showed that there was a moderate positive correlation between policy, knowledge of IT and education with security awareness and practice, but behavior factor has a low correlation. These results indicated that security awareness and practice level of employees at home are mostly at the middle level. It is hoped that the present study provides an initial step to focus on security training sessions among higher education employees to reflect new knowledge on the importance of security training to increase the knowledge of information security. It is hoped that the findings of this study will serve as a starting point for further research and focus on providing security information for public, which will help to reflect new knowledge on the importance of security training and increase awareness of information security.